Emotional Design in Concept Maps – No Support but Also No Burden - Lenski, Sina; Großschedl, Jörg (Frontiers in Education, 2022)
A concept map is a powerful method that promotes meaningful learning and is highly recommended for use in biology classes. According to multimedia research, the effectiveness of concept maps could be improved by incorporating pictorial elements. Apart from using realistic images, a new field of research claims that specific design manipulations, including human-like features with appealing colors (emotional design), influence learners’ affective state and improve learning. A positive affective state is assumed to evoke emotions and provoke deeper cognitive processing, which increases the cognitive resources available for a task. We conducted two experiments with a total of N = 249 junior high school students, comparing the effect of concept maps with emotional design illustrations (emotional design), with non-emotional design illustrations (neutral design), and without illustrations (control design). Experiment 1 examined the influence of these designs on students’ perceived affective state, perceived cognitive load (extraneous, intrinsic, and germane load), perceived task difficulty, and learning performance (n = 202), experiment 2 focused on the perceived affective state of the students (n = 47). We found that emotional design led to a significant decrease in perceived task difficulty, but we neither found an effect on learning performance nor the positive affective state. Learning with pictorial concept maps (in emotional or neutral design) reduced the negative affect compared to learning with control concept maps. Other than expected, the neutral design led to reduced perceived extraneous and intrinsic cognitive load. Consequently, in terms of learning, emotional design in concept maps did not hamper learning but did not foster it either.